Phage biobanks as enabling infrastructure for precision phage therapy in the era of antimicrobial resistance - Topa-Pila, Paulina; Morales, Katheryne Y.; Palacios-Mora, Doménica P.; Flores-Hernández, Cristina; Altamirano-Cisneros, Analía; Gavilanes, Joselyn Micaela; Villacís-López, Keyla; Arancibia, Mirari; Mora-Domínguez, Johanna; Calero-Cáceres, William (Frontiers in Antibiotics, 2026)
The renewed interest in bacteriophage therapy as a response to antimicrobial resistance (AMR) has exposed a critical barrier to its scalable implementation: the lack of structured infrastructure to support precision phage deployment. Due to their narrow host specificity, bacteriophages require timely access to well-matched candidates, making ad hoc isolation and informal exchange insufficient for routine therapeutic use. In this Perspective, we argue that phage biobanks must be redefined as enabling infrastructure rather than passive repositories. We propose that next-generation phage biobanks should integrate curated biological diversity, systematic genomic and functional qualification, and predictive capacity to support rapid phage–host matching. Together, these elements transform biobanks into decision-support systems capable of informing translational applications under time-sensitive conditions. This infrastructural model is particularly relevant within a One Health framework, where resistant pathogens circulate across human, veterinary, agricultural, and environmental domains. Rather than reviewing methodologies, we outline conceptual principles to guide the design of phage biobanks as integrated, predictive, and sustainable assets. We contend that the future impact of phage therapy will depend less on individual phage discovery than on the development of interoperable biobank infrastructures that enable precision antimicrobial interventions at scale.